Efficient Volumetric PolyCube-Map Construction - Fu, Xiao-Ming; Bai, Chong-Yang; Liu, Yang (Computer graphics forum, 2016)
PolyCubes provide compact representations for closed complex shapes and are essential to many computer graphics applications. Existing automatic PolyCube construction methods usually suffer from poor quality or time‐consuming computation. In this paper, we provide a highly efficient method to compute volumetric PolyCube‐maps. Given an input tetrahedral mesh, we utilize two novel normal‐driven volumetric deformation schemes and a polycube‐allowable mesh segmentation to drive the input to a volumetric PolyCube structure. Our method can robustly generate foldover‐free and low‐distortion PolyCube‐maps in practice, and provide a flexible control on the number of corners of Polycubes. Compared with state‐of‐the‐art methods, our method is at least one order of magnitude faster and has better mapping qualities. We demonstrate the efficiency and efficacy of our method in PolyCube construction and all‐hexahedral meshing on various complex models.